The programming primitives effects of the overlapping message-passing and computation in Beowulf cluster computing / Mohamed Faidz Mohamed Said - Mohamed Said, Mohamed Faidz (Institute of Graduate Studies, 2015)
Beowulf cluster computing is one of the parallel architectures that has been extensively utilized by exploiting the commodity aspect of its hardware and also the open codes of its software. It offers many advantages, but in order to support parallel and distributed applications, many factors of the cluster system have contributed to the performance bottleneck. One of these factors is due to the explicit primitives of its message-passing implementation. Basically, these primitives are divided into two types; blocking and non-blocking communications. For optimization purposes, the primitives can be applied to allow the overlap of the message-passing and computation to create an application with optimal completion time. However, the effects on the low-level issues concerning data overhead by using different primitives have not been explored in details. This research project empirically looks into the effect of the overlapping message-passing and computation in the proposed Beowulf cluster. It also develops new analytical tool to analyze the overlapping effect, particularly on the programming primitives characterizations…